2009
DOI: 10.1177/1049732309354277
|View full text |Cite
|
Sign up to set email alerts
|

“All at Sea”: The Experience of Living With Cystic Fibrosis

Abstract: In this qualitative study the researchers explored living with cystic fibrosis (CF)-a chronic, life-threatening, life-limiting disease that demands a relentless regime of daily treatment. The unique challenges and issue for care that CF presents were considered. Utilizing a phenomenological perspective, data drawn from unstructured interviews included narratives and drawings contributed by children, adolescents, young adults, and parents-eight families representing nine young people with CF. In line with van M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
40
1
3

Year Published

2011
2011
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 55 publications
3
40
1
3
Order By: Relevance
“…The participants did report finding meaning and positive benefits from facing their disease. These findings are similar to those of other studies of adolescents and young adults living with chronic illness who also reported a struggle to make meaning in the face of a life-threatening illness (Jessup & Parkinson, 2010;Taylor et al, 2010). According to Parry and Chesler (2005), reports of benefit finding and meaning making are signs of psychosocial thriving posttreatment; however, the isolation and lack of support reported by survivors could predispose this population to be at risk for psychological late effects.…”
Section: Discussionsupporting
confidence: 90%
“…The participants did report finding meaning and positive benefits from facing their disease. These findings are similar to those of other studies of adolescents and young adults living with chronic illness who also reported a struggle to make meaning in the face of a life-threatening illness (Jessup & Parkinson, 2010;Taylor et al, 2010). According to Parry and Chesler (2005), reports of benefit finding and meaning making are signs of psychosocial thriving posttreatment; however, the isolation and lack of support reported by survivors could predispose this population to be at risk for psychological late effects.…”
Section: Discussionsupporting
confidence: 90%
“…Perhaps the request to complete a set of questionnaires was seen as an added burden to their already busy lives caring for their child with CF (Jessup & Parkinson, 2010) and we strove to distance ourselves from the parents by distributing the study packs via the CF charity. This helped to assure respondents of their anonymity.…”
Section: Discussionmentioning
confidence: 99%
“…It occurs in approximately 1:2,500 live births (Australian Cystic Fibrosis Registry, 2013) and is life‐limiting (MacKenzie, Gifford, & Sabadosa, 2014). The intensive, daily, lifelong management of CF imposes heavy demands on families and children: the need for frequent hospital visits for ambulatory and inpatient care; navigating health care provided by a large multidisciplinary team; and increasing care complexity creating challenging decisions and interactions (Jessup & Parkinson, 2010). Families with children who have CF and who reside in regional, rural or remote locations have additional burdens related to access to services, travelling time and social isolation.…”
Section: Introductionmentioning
confidence: 99%
“…Most evidence relating to the experience of growing up with a long‐term condition and the impact this may have on a child's expected developmental trajectory (Venning, Eliott, Wilson, & Kettler, ) is quantitative and addresses the perspectives of older children and adolescents (e.g., Smith, Taylor, Newbould, & Keady, ) with diabetes, asthma, cystic fibrosis, and rheumatic conditions (see, e.g., Cartwright, Fraser, Edmunds, Wilkinson, & Jacobs, ; Jessup & Parkinson, ; Jonsson, Egmar, Hallner, & Kull, ; Marshall, Carter, Rose, & Brotherton, ). The impact and influence of a long‐term condition on adolescents tend to be reported in terms of the young people's resilience and how the young people adjust to and aim for control over the disruption associated with the condition (Cartwright et al., ; Ferguson & Walker, ; Tong, Jones, Craig, & Singh‐Grewal, ).…”
mentioning
confidence: 99%